2017
DOI: 10.1631/jzus.b1600256
|View full text |Cite
|
Sign up to set email alerts
|

Hyperechoic demarcation line between a tumor and the muscularis propria layer as a marker for deciding the endoscopic treatment of gastric submucosal tumor

Abstract: Minimally invasive endoscopic resection has been rapidly adopted as a new technique for treating patients with gastric submucosal tumors (SMTs) originating in the muscularis propria (MP) layer. This study was conducted to evaluate the information obtained from endoscopic ultrasonography (EUS) to determine the appropriate endoscopic dissection method for treating SMTs originating in the MP layer. Between February 2014 and May 2016, a total of 50 patients with gastric SMTs originating in the MP layer were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…A literature search demonstrated that there was still a lack of articles investigating risk factors using EUS images to predict perforation. Zhang et al analyzed 43 patients and found that more SMTs in the perforation group were located in the deep MP and had a length of the muscular connection ≥40% of the tumor capsular semi-circumference; however, they did not perform univariate or multivariate analyses [ 13 ]. Moreover, it was difficult to apply their findings in realistic situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature search demonstrated that there was still a lack of articles investigating risk factors using EUS images to predict perforation. Zhang et al analyzed 43 patients and found that more SMTs in the perforation group were located in the deep MP and had a length of the muscular connection ≥40% of the tumor capsular semi-circumference; however, they did not perform univariate or multivariate analyses [ 13 ]. Moreover, it was difficult to apply their findings in realistic situations.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasonography (EUS) is an important technique in the diagnosis of SMTs, as it can provide information on the layer from which the SMTs originate, as well as the size, borderline, and echoes to help evaluate the possible pathology of the SMTs [ 12 ]. Additionally, it can show information on the membrane integrity, spatial relationship between the tumor capsule and the serosal layer, and other factors that predict procedural complications and patients’ prognoses [ 13 ]. Zhang et al [ 13 ] showed that SMTs located in the superficial MP with a length of the muscular connection <40% of the tumor capsular semi-circumference may have a lower risk for perforation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, rectal NENs are increasingly frequently detected, with the widespread availability and accessibility of endoscopy and cross-sectional imaging modalities (Kos-Kudla et al, 2017). Multiple studies have shown that endoscopic ultrasound (EUS) is an advanced endoscopic technique and is currently used in the diagnosis and preoperative assessment of NENs (Kim, 2012;Liu et al, 2013;Zhang et al, 2017). However, EUS imaging of rectal NEN and differential diagnosis with other submucosal tumors (SMTs) has not been adequately reported.…”
mentioning
confidence: 99%
“…However, no penicillin resistance was found in this study, suggesting that the TEM gene may not be the major cause of the GBS resistance to penicillin. Finally, the ermB and mefA genes (Harimaya et al, 2007), which are closely related to the TetM gene for tetracycline resistance (Fischer et al, 2013), are worthy of further studies and may be associated with tumors (Hao et al, 2017;Zhang et al, 2017).…”
mentioning
confidence: 99%